Money Laundering and Financial Crimes in Nigeria - TIJJANI, AHMED T. (2018)
This paper, therefore, presents an evaluation of the strategies and future directions of money laundering in Nigeria, as it is a ‘new’, dynamic place in which to conduct business and the financial centre of the Nigeria. It examines the various ways in which legislation and law enforcement in Nigeria are struggling with and tackling the issues and problems of money laundering in the face of organised crime and terrorism. In this paper, the concepts of money laundering and financial crimes in Nigeria, with a special focus on strategies as well as future direction of control, are explored in some depth. This work has established that Nigeria has a substantial anti-money laundering framework; however, it suffers from some weaknesses. These weaknesses are caused by the poor relationship between anti-money laundering units, the Anti-Organised Crime Department of the Nigeria police, the financial sector and the Central Bank of Nigeria. This situation is particularly evident when it comes to sharing information on those suspected of money laundering in Nigeria. The ‘lack of a relationship’ is illustrated by primary research, as is the fact that other nations have (that is the UK) developed a more intelligence-led approach and partnerships in their quest to prevent money laundering where possible in their jurisdiction. This paper highlights the progress that is needed in Nigeria and the Nigerian to prevent money laundering, and as such is an original contribution to knowledge in an under-researched field in the Nigeria.